2015
DOI: 10.3109/09637486.2015.1064870
|View full text |Cite
|
Sign up to set email alerts
|

14 Days of supplementation with blueberry extract shows anti-atherogenic properties and improves oxidative parameters in hypercholesterolemic rats model

Abstract: The effects of supplementation with blueberry (BE) extract (Vaccinium ashei Reade) for 14 consecutive days on biochemical, hematological, histopathological and oxidative parameters in hypercholesterolemic rats were investigated. After supplementation with lyophilized extract of BE, the levels of total cholesterol, low-density lipoprotein cholesterol and triglycerides were decreased. Histopathological analysis showed significant decrease (p < 0.05) of aortic lesions in hypercholesterolemic rats. Oxidative param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…blood pressure, lipid profile, inflammation, and oxidative stress (see e.g. [ 37 42 ]). The beneficial effects were to a major part attributed to the polyphenols present.…”
Section: Discussionmentioning
confidence: 99%
“…blood pressure, lipid profile, inflammation, and oxidative stress (see e.g. [ 37 42 ]). The beneficial effects were to a major part attributed to the polyphenols present.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acai berry, native to the Amazon region, has been reported to increase serum activity of PON1 and levels of HDL cholesterol, and increase fecal cholesterol excretion in rat models of hyperlipidemia and hepatic steatosis [15,16,17]. Commonly consumed dietary berries, such as blueberries and strawberry extracts, have also been demonstrated to improve lipid profiles by downregulating the activity of genes related to fatty acid synthesis, causing regression of aortic lesions, as well as decreasing inflammation and oxidative damage in these animals [18,19]. Strawberry and blueberry pomace, a byproduct from industrial fruit processing, has emerged as a promising source of antioxidants and micronutrients, and has been tested for its health benefits by many researchers, mainly as an alternative and cost-effective way of supplementing the human diet with berry polyphenols.…”
Section: Review Methodsmentioning
confidence: 99%
“…The cardioprotective effects of blueberry ( Vaccinium ashei Reade) extract were investigated in hypercholesterolemic rats for 14 days. The result showed that blueberry extract decreased aortic lesions, reduced serum lipid profiles (total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and TG), and increased activities of antioxidant enzymes (CAT, SOD, and glutathione peroxidase (GSH-Px)) [69]. The effects of supplementation with blueberry for 10 weeks on endothelial function and BP were studied in rats fed a high-fat diet.…”
Section: Experimental Studiesmentioning
confidence: 99%